2004
DOI: 10.1007/bf03018546
|View full text |Cite
|
Sign up to set email alerts
|

The posterior lumbar plexus (psoas compartment) block and the three-in-one femoral nerve block provide similar postoperative analgesia after total knee replacement

Abstract: P Pu ur rp po os se e: : To compare the efficacy of a continuous posterior lumbar plexus (PSOAS) block to a continuous three-in-one femoral nerve (FEM) block in patients undergoing primary total knee replacement (TKR).M Me et th ho od ds s: : Sixty patients were randomly allocated to receive iv patient-controlled morphine analgesia (PCA), PCA plus a continuous FEM block with 30 mL ropivacaine 0.5% and epinephrine 1:200,000 bolus followed by an infusion of ropivacaine 0.2% at 12 mL·hr -1 for 48 hr, or PCA plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 23 publications
(34 reference statements)
6
61
2
1
Order By: Relevance
“…McNamee et al [5] affirm that the addition of an obturator nerve block improved postoperative analgesia following total knee replacement; however, while our results show a higher rate of obturator nerve involvement in the PSOAS group, there were no differences between the two techniques in terms of VAS pain scores and total morphine consumption after TKR. In agreement with our trial, Kaloul et al [8] suggest that obturator nerve involvement does not improve postoperative pain scores after TKR; Morin et al [9] come to the same conclusion. Preliminary results by Lund et al go in the opposite direction: continuous adductor-canal-blockade may be a valuable adjunct for post-operative analgesia after major knee surgery [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…McNamee et al [5] affirm that the addition of an obturator nerve block improved postoperative analgesia following total knee replacement; however, while our results show a higher rate of obturator nerve involvement in the PSOAS group, there were no differences between the two techniques in terms of VAS pain scores and total morphine consumption after TKR. In agreement with our trial, Kaloul et al [8] suggest that obturator nerve involvement does not improve postoperative pain scores after TKR; Morin et al [9] come to the same conclusion. Preliminary results by Lund et al go in the opposite direction: continuous adductor-canal-blockade may be a valuable adjunct for post-operative analgesia after major knee surgery [12].…”
Section: Discussionsupporting
confidence: 92%
“…This could *Address correspondence to this author at the Via Di S. Eufemia, 11, 00187 Rome, Italy; Tel: +39-06-6793660; Fax: +39-06-6793660; E-mail: mario.dauri@fastwebnet.it be explained considering that the three-in-one block does not involve the posterior branch of the obturator nerve [6], resulting in a less consistent blockade of this nerve than the lumbar plexus block (PSOAS) [5,7]. However, Kaloul et al [8] and Morin et al [9] found no differences in postoperative pain relief comparing continuous lumbar plexus and femoral blockades, after TKR. None of these previous studies explored intra-operative time, nor did they use ultrasoundguided techniques.…”
Section: Introductionmentioning
confidence: 99%
“…El bloqueo lumbar no está recomendado actualmente como tratamiento del dolor agudo postoperatorio de la PTR (recomendación C, evidencia 3), pues la analgesia proporcionada es similar a la obtenida con el bloqueo femoral, pero con un índice más alto de posibles complicaciones derivadas de la técnica 98 .…”
Section: Analgesia Epiduralunclassified
“…They concluded that the obturator nerve does not have a significant contribution for the development of postoperative pain in TKA. Kaloul et al 27 reached to the same conclusion regarding morphine consumption using those same techniques in two groups of 20 patients. The intercurrences observed included two cases of nausea and/or vomiting, of low severity, in each group.…”
Section: Discussionmentioning
confidence: 57%